Justiniano, emperador de los romanos. González Fernández, Rafael. Editorial Síntesis. Madrid, 2020, 354 pp. ISBN: 978-84-1357-036-5 - Martínez Sánchez, Miguel (Antigüedad y Cristianismo, 2023)
Recensión